Blennioids (Blennioidea) of the Slovenian coastal waters - Lipej, Lovrenc (Annales. Series historia naturalis, 1999)
Although the research of Blennioidea (blennies and their relatives) has a long_standing tradition in the Adriatic, only a few data exist in the occurence of this littoral fish assemblage in the Gulf of Trieste. The paper presents the checklist of blennioids in the Slovenian coastal sea. Altogether 18 blennioids were recorded in the studied area. 14 of them were blennies (fam. Blenniidae), 3 threefin blennies (gen. Tripterygion) and 1 blennioid species from the family Clinidae...
Keywords: babice; Blennioidea; Blennioidei; prevalence; razširjenost; ribe; slovensko morje